The effect of femoral component rotation on the extensor retinaculum of the knee - Ghosh, K.M.; Merican, A.M.; Iranpour, F.; Deehan, D.J.; Amis, A.A. (Wiley-Blackwell, 2010)
Malrotation of the femoral component may cause patellofemoral complications after total knee replacement (TKR). We hypothesized that femoral component malrotation would cause excessive lengthening of the retinacula. Retinacular length changes were measured by threading fine sutures along them and attaching these to the patella and to displacement transducers. The knee post-TKR was flexed-extended while the quadriceps were tensed, then the measurements repeated after rotating the femoral component 5 degrees internally and then 5 degrees externally. Internal rotation shortened the medial patellofemoral ligament (MPFL) significantly from 100 degrees to 0 degrees extension. External rotation lengthened the MPFL significantly from 90 degrees to 0 degrees extension. The transverse fibers of the lateral retinaculum showed no significant differences. The MPFL attaches directly from bone to bone, so it was lengthened directly by movement of the trochlea and patella, whereas the deep transverse fibers of the lateral retinaculum attach to the mobile iliotibial tract, so they were not lengthened directly. (C)2010 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 28:1136-1141, 2010